The Cys-His motif of Ty3 NC can be contributed by Gag3 or Gag3-Pol3 polyproteins. - Orlinsky, K J (1994)
The major structural proteins capsid and nucleocapsid (NC) of the Saccharomyces cerevisiae retroviruslike element Ty3 are produced as domains within the Gag3 and Gag3-Pol3 precursor polyproteins. Ty3 NC contains one copy of the conserved motif CX2CX4HX4C found in most retroviral NC proteins. We show here that NC proteins derived by processing of these different precursor species differ at their carboxyl termini. To determine whether the Cys-His motifs of these nascent NC domains contribute differently to replication, Gag3 and Gag3-Pol3 fusion proteins containing wild-type or mutant Cys-His domains were expressed from separate constructs. Although the Cys-His box was shown to be essential for polyprotein processing of a wild-type Ty3 element, this domain could be contributed from Gag3 or as part of Gag3-Pol3. These data suggest that the functions of the retroviral NC Cys-His domain contributed from Gag and Gag-Pol are redundant.